A new species of Rhopalopsole (Insecta, Plecoptera, Leuctridae) from the Anhui Province of China and phylogeny of Leuctridae based on mitochondrial genomes - Xiao Yang; Yu-Zhou Du (ZooKeys)
A new species of Leuctridae (Plecoptera) from Anhui Province of China, Rhopalopsole gibba sp. nov., is described and illustrated. The new species is compared to a similar species, R. dicondylica Yang & Du, 2021. We sequenced the complete mitochondrial genome of the new species and found a length of 16,157 bp. Phylogenetic analysis based on 10 complete or nearly complete mitogenomes of four genera of Leuctridae from China showed the following phylogenetic relationships: ((Rhopalopsole + Perlomyia) + Paraleuctra) + Leuctra. Finally, the geographical distribution of Leuctridae in China is preliminarily summarized.